Unravelling Teachers’ Beliefs about TPACK in Teaching Writing during the Covid-19 Pandemic - Lailatun Nurul Aniq; Nur Arifah Drajati; Endang Fauziati (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this research is to explore the teacher’s belief about TPACK in teaching writing during the Covid-19 pandemic era. It is in regards to content, technology, and pedagogy that in-service EFL teachers reflect appropriate technology integration and proper teaching strategy that support teaching writing during the Covid-19 pandemic era. This case study used semi-structured interviews and artefact analysis. Three in-service EFL teachers participated in this study. Although there were significant differences in their practical views, this study found how teachers elaborate their belief about in teaching writing, i.e. utilizing familiar smartphones apps, engaging content-based curriculum, and applying student-oriented teaching method. Moreover, the study confirms previous findings of the importance of TPACK in the EFL context. The study highlights the need for the acknowledgement of practical ways in classroom practice of the TPACK framework in teaching writing. Finally, this study might have implications for educational institutions to provide a better improvement in the future.